Impact of discharge criteria on the length of stay in preterm infants: A retrospective study in Japan and Finland - Itoshima, Ryo (Elsevier, 2025)
Background: To shorten the hospital stay in preterm infants, it is important to understand the factors extending the length of stay.
Aims: To understand how different discharge criteria affect the length of stay in preterm infants.
Study design: A retrospective comparison study.
Subjects: Preterm infants born at 28 to 31 gestational weeks in 2020-2021 in a Level IV NICU in Japan (n = 22) and a Level III NICU in Finland (n = 49).
Outcome measures: We compared the most common last discharge criteria and the postmenstrual age (PMA) between the two NICUs. The potential extending effects of each discharge criterion on the length of stay were also evaluated. The discharge criteria were classified into six categories: temperature, respiration, feeding, examination, weight limit, and family readiness.
Results: The PMA at discharge was significantly higher in Japan than in Finland: median 40.7 (interquartile range 39.9-41.3) vs. 37.9 (36.9-39.0) weeks; r = 0.58; p < 0.001. The most common last discharge criterion was the family criterion in Japan (n = 19; 86 %) and the respiration criterion in Finland (n = 43; 88 %). In Japan, the length of stay was extended by 7.9 (standard deviation [SD] 7.0) days due to a lack of family readiness for discharge and 8.7 (SD 8.7) days due to not having discharged home with a feeding tube as a common practice.
Conclusions: The length of stay of preterm infants in Japan could be notably reduced by supporting the parents' earlier readiness for discharge and allowing tube feeding at home.